PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIANPRODUK WARDAH (Studi Kasus Pada Konsumen Wardah Kota Bengkulu) - Lucky Ampriyanti; Sri Ekowati (UM. Bengkulu, 2022)
This study aims to determine the effect of product quality and price on wardah product purchasing decisions (a case study of Wardah consumers in Bengkulu City), either partially or simultaneously. There are several factors that will be discussed in this study, including Product Quality (X1) and Price (X2). The object of this research is the consumers of Wardah Bengkulu City, amounting to 96 people. In this research, the writer uses the method of data collection by means of observation, distributing questionnaires and interviews. There are several data analysis techniques used in this study, including by using instrument test, classical assumption test, respondent analysis analysis, multiple linear regression analysis, determinant coefficient, and hypothesis testing. From the results of the tests that have been carried out, it can be concluded that the variables of Product Quality (X1) and Price (X2) have partially or simultaneously affected Wardah Product Purchase Decisions (Case Study on Wardah Consumers, Bengkulu City). From the results of the multiple linear regression test, the regression equation is as follows: Y = 2.274 + 0.471 (X_1) + 0.416 (X2). Keywords: Product Quality, Price and Purchase Decision